Systemic family therapy in multiprofessional complex of treatment and rehabilitation of schizophrenia spectrum disorders - S. E. Medvedev; A. P. Kotsiubinsky; B. G. Butoma; O. Yu. Zadonskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article based on systemic approach to family therapy presents the isomorphism of relationship structure in the family of identified patient and multiprofessional teаm of caring service professionals. Mental health service is organized to help the patient. Its effectiveness is determined by the improvement of the patient undergoing treatment and rehabilitation, thereby increasing the adaptive capacity of the patient and his return to society. Successful social integration of the patient largely depends on the level of his social competence. The study includes 23 women and 21 men aged from 18 to 30 participating in the biopsychosocial rehabilitation program for at least 12 months. Patients from the families, which took part in the psychotherapeutic work, showed an increase of social competence with Social Quotient (SQ) escalation for more than 15% in three months and more than 32% in 12 months after the start of the rehabilitation program compared to the baseline. The results of the work allow formulating recommendations for carrying out the effective program which includes psychotherapeutic interventions, sociotherapeutic events, as well as the appropriate balance of the various forms of specialized medical care, depending on the current stage of mental disorders. This is currently considered to be а personalized medicine.